ANALYSIS OF NETWORK SERVICE ACTIVITIES IMPROVEMENT AT PT. ABC - Rizki Ahmad Fauzi (STIE Binaniaga, 2016)
This research aims to identify a chain of network services that should have to be improved considering to the level of needs and customer service satisfaction. Understanding about the services conditions based on the level of its needs and customer satisfaction requirements, then the company is able to perform the priority of its improvement. This research has identified the sampling taken from ABC’s customers and have implemented the Important Performance Analysis Method. Several factors have been evaluated are as follows: Stable network (non intermitten); Network which has never had problems.; Network which has never had repeated problems;Speed of accessible network is in compliance with the contract.; Data application runs well; Sound/voice application is good;Internet application runs well; Service Level Ability is in compliance with the contract and Guarantee coverage is in compliance with the agreement. Having had research of the aforementioned factors, there are three factors need to be improved as the priority; stable network, network which has never had problem, and network which has never had repeated problem.Keywords : network services, customer satisfaction, performance importance analysis.